GENOTYPING OF HOLSTEIN FRIESIAN CROSSBRED CATTLE FOR CVM AND FXI DEFICIENCY LOCI - S.B. Khade; V.D. Pawar; A.Y. Doiphode; M.P. Sawane; U.D. Umrikar (Indian Journal of Veterinary and Animal Sciences Research, 2024)
In animal breeding, genetic disorders are one of the most important issues for breeders. The present study was carried out to genotype HF crossbred cattle for FXI deficiency and CVM using PCR and PCR-RFLP using 50 blood samples. Amplicons of 244 bp for FXI gene and the 287 bp for SLC35A3 gene were successfully amplified. Analysis of amplicons of FXI gene revealed single 244 bp fragment which indicates absence of mutant allele. The amplicons of 287 bp of SLC35A3 gene was digested with Pst I RE which revealed two fragments of size 264 bp and 23 bp for normal animals. In the present study, out of fifty HF crossbred animals screened neither carrier nor affected animals were found for FXID and CVM.